Graph Application of Social Network AI Language Understanding and Reasoning - Lu, Miao (Journal of Artificial Intelligence and Information, 2025)
With the booming development of social networks, the value contained in social big data is increasingly prominent. This article focuses on the analysis of social network language understanding and reasoning techniques based on knowledge graphs. It systematically explores the construction methods of knowledge graphs, the semantic understanding mechanism of social texts, and the key tasks of reasoning decisions. It proposes a social language understanding framework that integrates knowledge graphs and deep learning, and provides technical implementation paths for specific tasks. The research aims to fully tap into the value of social data, enhance the intelligence level of social networks, and provide new ideas and methods for related research.